Effects of climatic seasonality on the isotopic composition of evaporating soil waters - P. Benettin; T. H. M. Volkmann; J. von Freyberg; J. von Freyberg; J. Frentress; D. Penna; T. E. Dawson; J. W. Kirchner; J. W. Kirchner; J. W. Kirchner (Hydrology and Earth System Sciences, 2018)
Stable water isotopes are widely used in ecohydrology to trace the transport, storage, and mixing of water on its journey through landscapes and ecosystems. Evaporation leaves a characteristic signature on the isotopic composition of the water that is left behind, such that in dual-isotope space, evaporated waters plot below the local meteoric water line (LMWL) that characterizes precipitation. Soil and xylem water samples can often plot below the LMWL as well, suggesting that they have also been influenced by evaporation. These soil and xylem water samples frequently plot along linear trends in dual-isotope space. These trend lines are often termed "evaporation lines" and their intersection with the LMWL is often interpreted as the isotopic composition of the precipitation source water. Here we use numerical experiments based on established isotope fractionation theory to show that these trend lines are often by-products of the seasonality in evaporative fractionation and in the isotopic composition of precipitation. Thus, they are often not true evaporation lines, and, if interpreted as such, can yield highly biased estimates of the isotopic composition of the source water.